1979
DOI: 10.1063/1.326549
|View full text |Cite
|
Sign up to set email alerts
|

A barrier model for ZnO varistors

Abstract: A model of current transport in ZnO varistors is proposed. The model is a modification of an earlier one suggested by Levine, with the major difference being the inclusion of a thin (?10 Å) ’’disordered’’ layer which separates the single-crystal ZnO grains. The proposed model is shown to be consistent with electrical and microstructural observations and can satisfactorily account for α’s in excess of 60. A technique for extracting the surface-state density Ns(E) and doping profiles from C-V and I-V data is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
3

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(32 citation statements)
references
References 11 publications
2
27
0
3
Order By: Relevance
“…1.The XRD pattern of pure ZnO( In the case of Ag-ZnO Nps the intensity of peak is reduced due to the formation of Ag nanoparticles on the surface of ZnO Nps [30] . A broad peak at 3434 cm -1 (stretching) and 1330cm -1 to 1670 cm -1 (bending) indicates the presence of hydroxyl residue which is due to atmospheric moisture [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…1.The XRD pattern of pure ZnO( In the case of Ag-ZnO Nps the intensity of peak is reduced due to the formation of Ag nanoparticles on the surface of ZnO Nps [30] . A broad peak at 3434 cm -1 (stretching) and 1330cm -1 to 1670 cm -1 (bending) indicates the presence of hydroxyl residue which is due to atmospheric moisture [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…32,33 However, the microscopic origins of DSB are still un-fully identified, 32 though various models have been proposed focusing on the conduction mechanism since the discovery of non-ohmic properties of ZnO varistors by Matsuoka, 34 including the successful description by Pike, Blatter and Greuter. 1,33,35,36 So far, the intergranular layer, 34 segregation of additives, 37,38 thin disordered layer, 39 oxygen-excess defects like chemisorbed oxygen or excess amount of oxygen, 40,41 native point defects such as zinc vacancy (V Zn ) and oxygen interstitial (O i ), 2,15,42 and certain complex defect composed of additives and native defects 43 have all been considered as the possible candidates for promoting the generation of acceptor-states. In effect, recent successes in performing first-principles calculations on ZnO materials to consider the grain boundary structure, 2,32 dopant segregation 44 and defect formation [43][44][45] have made it possible to understand the formation of acceptor state from atomic scale.…”
Section: A Formation Of Double-schottky Barriermentioning
confidence: 99%
“…[1][2][3][4][5] Also, several models have been proposed to explain the degradation phenomena. 2,6-9) Eda et al 7) reported that the degradation occurred due to a reduction of the barrier height caused by the migration of two types of the ions that exist in the intergranular or the depletion layers.…”
Section: Introductionmentioning
confidence: 99%